2018
DOI: 10.1021/acs.molpharmaceut.8b00947
|View full text |Cite|
|
Sign up to set email alerts
|

Polymer-Mediated Drug Supersaturation Controlled by Drug–Polymer Interactions Persisting in an Aqueous Environment

Abstract: We investigated the drug–polymer interactions in nonaqueous and aqueous environments between a poorly water-soluble drug, BAY1161909 (909), and two commonly used polymers in amorphous solid dispersions, i.e., PVP and HPMC-AS. In an nonaqueous state, with a drug–polymer Flory–Huggins interaction parameter, solution NMR and FT-IR results revealed that strong specific interactions existed between 909 and PVP, while not between 909 and HPMC-AS. After prolonged moisture exposure under 95% RH, 909/PVP intermolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…It has been discussed that polymers exhibiting a high hydrophilicity tend to preferably interact with water, which is also highly hydrophilic rather than with the hydrophobic drug substance [38]. Chen et al emphasized that interactions between a highly hydrophilic polymer with a hydrophobic drug are "water-vulnerable", which means that the interactions between the polymer and the drug become weaker over time, while the interactions between the polymer and water become stronger [16]. This fact is perfectly in line with our data from the supersaturation assay, where the supersaturation in presence of PVA dramatically crashed after a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been discussed that polymers exhibiting a high hydrophilicity tend to preferably interact with water, which is also highly hydrophilic rather than with the hydrophobic drug substance [38]. Chen et al emphasized that interactions between a highly hydrophilic polymer with a hydrophobic drug are "water-vulnerable", which means that the interactions between the polymer and the drug become weaker over time, while the interactions between the polymer and water become stronger [16]. This fact is perfectly in line with our data from the supersaturation assay, where the supersaturation in presence of PVA dramatically crashed after a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it was shown that hydrogen bonds between drug and polymer are decisive in order to avoid AAPS upon contact with moisture [11,14,15]. On the other hand the presence of hydrogen bonds alone was often shown to be not sufficient to generate a satisfactory maintenance of the supersaturated state in solution upon dissolution of the ASD [16]. A few studies investigated ternary ASDs with a combination of hydrophilic and hydrophobic polymers and showed a benefit compared to the respective binary ASD formulation, by achieving optimized dissolution rate and supersaturation maintenance [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The shift of the glass transition temperatures towards lower temperatures and the occurrence of two distinct glass transition temperatures also indicated a formation of an AAPS and a disruption of interactions between drug and polymer. The lower glass transition temperature reflected the drug-rich phase and the higher one corresponded to the polymer-rich phase (46,47).…”
Section: Phase Separation Upon Immersion In Hydrochloric Acidmentioning
confidence: 98%
“…The diffusion process of the release of the active substance from the matrix can be described by Korsmayer-Peppas equation [52,53] C D (t) = k r t n , (15) where k r is the rate of the release process and depends on the external conditions during the experiment, the glass transition temperature T g of polymer, and the hydrophilicity and structure of the matrix [54]. It is important to note that n indicates the dominant mechanism of the release process for cylindrical sample: 0.45 indicates Fickan diffusion (Case I), 0.85 is Case II (when domination of polymer stress relaxation process occurs), and 0.45 < n < 0.85 means anomalous diffusion (non-Fickan) [55,56].…”
Section: Theoretical Description Of the Release Of The Active Substancementioning
confidence: 99%
“…Despite the growing interest in understanding drug-carrier interactions at a molecular level, prediction of the drug release kinetics remains challenging due to many interrelated physicochemical processes that occur simultaneously in the aqueous environment [14,15]. Therefore, studies on the interaction of active substances (drugs) and their carriers in hydrous medium are important as they provide the basic foundation for their application [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%